(3EJMGa GdCNUG HaVGFd GdeSLO GdCbUis - (3GHf CHj TQja , eMeO Hf eMeO Hf CHj HcQ Hf Ydj GdebOSj, ceGd GdOjf CHh GdeYGd,J (B906 (3g` s ((3YdGAGdOjf Hf ehSi Hf Ydi GdYSjdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LdJ fYeGDg Yf GdEMUG hYdJ BdGDg Yf Cf JYO Ch JMUi Ch JSJbUi hHYO, adeG GQGO CHj GdTQY hQO Ydi YRei GdSGcf s
(3BNQgG (B:s
(3Jhdi GeQi HjOc hdG Jcdi Edi faSi hdG Edi CMO ShGc EdG Gddg HUjQ GdCehQ hcGf GdaQGZ ef JCdjag s
(3GYJeO ai JCdjag hJQJjHg Ydi cJGH (B"(3GdQhV GdeZQS ai aVd HjJ GdebOS(B"s
(3dJGL GdOjf YHOGdhgGH GdMSjfi GdOeTbi GdTGaYi ceG PcQ UGMH cTa GdXfhfs
(3hPcQ GdSjO eQJVi GdRHjOi UGMH JGL GdYQhS Cf eDda gPG GdcJGH TeS GdOjf eMeO Hf CMeO Hf CMeO GdefgGLi GdSjhWs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs